First Record of the sea turtle barnacle Chelonibia testudinaria (Linnaeus, 1758) in the Syrian Shore Line (Latakia University Journal -Biological Sciences Series, 2022)
During the comparative ecological study of the Biocenoses structure of the family Mytilidae (class Bivalvia) in the shore of Latakia, for the first time an individual of the species Chelonibia testudinaria was found during the collection of benthic samples from the Afamia area on 28/08/2021, where it was observed attached to a moulted piece of a dead loggerhead sea turtle carapace (Caretta caretta) on the shore of the Afamia area.This species is of Atlantic origin and has not previously been recorded anywhere on the Syrian shore.